Withholding Information on Unapproved Drug Marketing Applications: The Public Has a Right to Know. Issue 4 (2017) - Almashat, Sammy; Carome, Michael
Abstract : The Food and Drug Administration (FDA), as a matter of long-standing policy, does not inform the public of instances whereby applications for new drugs or new indications for existing drugs have been rejected by the agency or withdrawn from consideration, nor does it disclose the agency's analyses of the data submitted with such applications. This lack of transparency is unjustified and prevents patients, researchers, and healthcare providers from gaining insight into why a drug's application was not approved. The FDA's policy is particularly troubling in cases where the agency has found a currently marketed drug to be ineffective or unsafe for a newly proposed indication. Disclosure of the FDA's findings in such cases would promote public health by encouraging healthcare providers to avoid prescribing drugs for unapproved (off-label) uses that the agency has deemed to be potentially dangerous or ineffective. The FDA's counterpart agencies in Europe and Canada have demonstrated the feasibility of disclosing information on rejected and withdrawn drug marketing applications. The FDA should follow suit and allow the American public to know when a drug is deemed unsafe or ineffective for a certain use.